2022
DOI: 10.1103/physrevapplied.18.034046
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Dependent Interlayer Chiral Exchange and Field-Free Switching

Abstract: Interfacial Dzyaloshinskii-Moriya interaction (DMI) has long been observed in normal metal/ferromagnetic multilayers, enabling the formation of chiral domain walls, skyrmions and other 2D antisymmetric spin textures confined within a single ferromagnetic layer, while more recent works on interlayer DMI reveal new pathways in realizing novel chiral 3D spin textures between two separate layers. Here, we report on interlayer DMI between two orthogonally magnetized ferromagnetic layers (CoFeB/Co) mediated by a Pt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Current-induced field-free switching based on IEC has been demonstrated, , although the switching behavior is sometimes restricted by a small effective field or the thickness of the NM layer. To date, understandings of IEC-assisted field-free switching are constrained to a macroscopic symmetry-breaking point of view. , In other words, the IMA layer applies an effective in-plane (IP) field on the PMA layer via symmetric IEC. ,,, The effects of chiral IEC have not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Current-induced field-free switching based on IEC has been demonstrated, , although the switching behavior is sometimes restricted by a small effective field or the thickness of the NM layer. To date, understandings of IEC-assisted field-free switching are constrained to a macroscopic symmetry-breaking point of view. , In other words, the IMA layer applies an effective in-plane (IP) field on the PMA layer via symmetric IEC. ,,, The effects of chiral IEC have not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetization switching behavior is also governed by the characteristic DMI vector D, which defines both the strength and direction of the chiral exchange, and subsequently the switching polarity. Harnessing i-DMI to achieve field-free switching also eliminates the possibility of bipolar switching since the magnetization configuration reinitializes itself under the applied current [33]. These features are all essential for realizing practical SOT-MRAM.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow for writing and deleting operations, which are necessary when the different magnetic textures are employed as bits. Furthermore, the IL-DMI can allow for field-free switching as recent studies have shown. , This pure electrical switching facilitated by the IL-DMI offers new possibilities for spintronic devices while the IL-DMI is relatively simply induced by an oblique sputtering technique or a magnetic field during deposition . Conventionally, the strength of both DMI and IL-DMI is set during sample growth.…”
mentioning
confidence: 99%
“…Another route toward Hopfions is offered by the antisymmetric interlayer exchange interaction, which has been termed as RKKY-DMI or interlayer DMI (IL-DMI). It favors spin canting between layers in the lateral direction and originates from in-plane symmetry breaking. This allows for a highly sought-after tuning mechanism for 3D magnetic textures, which could stabilize such structures in magnetic multilayers without confinement.…”
mentioning
confidence: 99%
See 1 more Smart Citation